Gibbosaverruca weijiai, a new verrucid (Crustacea, Thoracica) species from the Weijia Guyot deep-sea seamount in the West Pacific - Gan, Zhibin; Zhang, Dongsheng; Li, Xinzheng; Wang, Chunsheng (European Journal of Taxonomy, 2021)
A new species of verrucid barnacle, Gibbosaverruca weijiai sp. nov., is described and illustrated based on specimens collected from a deep-sea seamount, Weijia Guyot, in the West Pacific. This is the third barnacle species reported from Weijia Guyot. The new species is distinguished from its congeners by its extremely long caudal appendage. In terms of shell morphology, G. weijiai sp. nov. is most similar to G. gibbosa and G. sulcata but differs from them by the intermediate articular ridges of its movable tergum and scutum, which are distinctly wider than the axial ridges. The COI and 16S rRNA sequences of the holotype of G. weijiai sp. nov. are presented to support future research, and a key to extant species of the genus Gibbosaverruca Young, 2002 is provided.